2004
DOI: 10.1055/s-2004-827233
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds fromBaseonema acuminatumLeaves: Isolation and Antimicrobial Activity

Abstract: Three new phenolic compounds, 1-galloyl-beta-D-glucopyranosyl-(1-->4)-beta-D-galactopyranoside (1), 2-methoxy-5-(1 '2 3'-trihydroxypropyl)-phenyl- 1-0-(6"-galloyl)-beta-D-glucopyranoside (2),and 2-methoxy-5-hydroxymethyl-phenyl-1-O-(6"-galloyl)-beta-D-glucopyranoside (3), together with the known compounds benzyl 6'-O-galloyl-beta-D-glucopyranoside (4), 1,6-di-O-galloyl-beta-D-glucopyranose (5), myrciaphenone B (6), kaempferol 3-0-(6"-galloyl)-beta-D-glucopyranoside (7), quercetin 3-0-(6"-galloyl)-beta-D-glucop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…are rich in galloylquinic acids and flavonoids ( Figure 1 ) [ 5 ]. De Leo et al [ 30 ] reported that phenolic compounds, mostly galloylquinic acid derivatives and flavonoids, were isolated from Baseonerna acuminatum P. Choux ( Asclepiadaceae ). According to these authors, 2-methoxy-5-(1′,2′,3′-trihydroxypropyl)-phenyl-1- O -(6″-galloyl)-beta- d -glucopyranoside, 2-methoxy-5-hydroxymethyl-phenyl-1- O -(6″-galloyl)-beta- d -glucopyranoside, benzyl 6′- O -galloyl-beta- d -glucopyranoside, and 1,6-di- O -galloyl-beta- d -glucopyranose were active against clinical and ATCC Candida albicans strains.…”
Section: Resultsmentioning
confidence: 99%
“…are rich in galloylquinic acids and flavonoids ( Figure 1 ) [ 5 ]. De Leo et al [ 30 ] reported that phenolic compounds, mostly galloylquinic acid derivatives and flavonoids, were isolated from Baseonerna acuminatum P. Choux ( Asclepiadaceae ). According to these authors, 2-methoxy-5-(1′,2′,3′-trihydroxypropyl)-phenyl-1- O -(6″-galloyl)-beta- d -glucopyranoside, 2-methoxy-5-hydroxymethyl-phenyl-1- O -(6″-galloyl)-beta- d -glucopyranoside, benzyl 6′- O -galloyl-beta- d -glucopyranoside, and 1,6-di- O -galloyl-beta- d -glucopyranose were active against clinical and ATCC Candida albicans strains.…”
Section: Resultsmentioning
confidence: 99%
“…An oxidative deglucosidation would convert gallomyrtucommulones C and D ( 3c and 3d ) into the G3 precursor 5 (Scheme ), making it of interest to evaluate the physiological relationship (if any) between G3 and these compounds. On the other hand, it was also interesting to investigate the antibacterial activity of gallomyrtucommulones, since powerful antibiotic activity has been shown for several phloroglucinols from myrtle. , All compounds were evaluated against a panel of resistant Staphylococcus aureus strains (Table ), and these included MRSA strains XU212 (which also expresses the TetK efflux pump) and EMRSA-15 (which is an epidemic MRSA strain commonly encountered in the U.K.). Other isolates included the multidrug-resistant SA-1199B, which overexpresses the NorA MDR efflux transporter, and RN4220, which has a more specific macrolide efflux mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Yazdani et al [53] reported that certain phenolic compounds isolated from the methanolic extracts of Piper betle L. (Piperaceae) could inhibit the growth of A. flavus . Phenolics isolated from the root bark of Lycium chinense Miller (Solanaceae) [54], the leaves of Baseonema acuminatum (Apocynaceae) [55], and the leaves of Hyssopus officinalis [56] have been associated with the antifungal and antioxidant activities. The bioactivity of phenolic compounds might be attributed to the interferece with proteins and forming non-covalent bonds leading to conformation changes and protein inactivation in microbes [57].…”
Section: Discussionmentioning
confidence: 99%